Design of a Single-Lens Freeform-Prism-Based Distortion-Free Stereovision System - Xiaoyu Cui; Liqian Wang; Yuetian Ren; Shuo Chen; Yue Zhao; Kahbin Lim; Tianxing Gong (IEEE Photonics Journal)
Stereo vision can be achieved with a single camera aided by a flat-face prism. However, large optical distortions may be caused by irregular refraction. To mitigate this deficiency and minimize distortion, a new freeform prism design is proposed to replace the flat-face prism. All refracting surfaces of the prism are designed for freeform features, which can process object points at a large depth of field. Differential equations are derived to express the freeform surface, and the Runge–Kutta method is used to numerically solve the differential equations.